Occurrence and use of tree species in the Hardtwald forest stands close to the city of Karlsruhe compared to the early 19th century - Obel, Carolin; Bussmann, Rainer W (Ethnobotany Research and Applications, 2025)
Background: Forest use in Central Europe has changed significantly in the last centuries. This is particularly the case near settlements, where, apart from wood production, forest use has changed from agricultural use to recreational use. The aim of the study was to compare the differences in tree species composition resulting from the changes in forest use in an urban forest close to the city of Karlsruhe, Germany. Additionally, this study aims to summarize changes in the usage of frequently occurring tree species. Furthermore, the extent to which the use of the species mentioned in the book compares with other regions in the world was examined. Methods: Historic information on tree species occurrence and usage was derived from C. C. Gmelin's "Nothülfe gegen Mangel aus Mißwachs" (Emergency Relief Against Deficiencies in Growth), an ethnobotanical work from 1817 and herbarium specimens. Information on recent species composition and usage was assessed in field surveys, and a literature survey.. For ethnobotanically useful species historical and recent occurrences and usage were compared and discussed . Results: Our results indicate a decline in ethnobotanically useful tree species in the last two centuries. Most prominently species from the Rosaceae and other tree species used due to their fruits were absent in the current survey. This indicates a changed species composition compared to 1817 within the Hardwald forest. The change in the species composition can be attributed primarily to the shift in forest use compared to earlier times, as well as to the different environmental conditions. A decline in stone fruit species and an increase in "future tree species" can be observed, as these are better adapted to the changed conditions. Conclusions: The use of the Hardwald forest has changed from a commercial forest with livestock farming to a local recreation area according to PEFC standards. It can be determined that 52.17% of the species in other areas are still used according to the possibilities presented in Gmelin's book. Keywords: 19th century ethnobotany, vegetation. change, usage change,, Germany, Baden-Württemberg, Karlsruhe